Ruminococcus bovis sp. nov., a novel species of amylolytic Ruminococcus isolated from the rumen of a dairy cow. Issue 8 (11th August 2021) - Gaffney, James; Embree, Jordan; Gilmore, Sean; Embree, Mallory
Abstract : This study describes JE7A12 T (=ATCC TSD-225 T =NCTC 14479 T ), an isolate from the ruminal content of a dairy cow. Phenotypic and genotypic traits of the isolate were explored. JE7A12 T was found to be a strictly anaerobic, catalase-negative, oxidase-negative, coccoid bacterium that grows in chains. The API 50 CH carbon source assay detected fermentation of d -glucose, d -fructose, d -galactose, glycogen and starch. HPLC showed acetate to be the major fermentation product as a result of carbohydrate fermentation. Phylogenetic analysis of JE7A12 T based on 16S rRNA nucleotide sequence and amino acid sequences from the whole genome indicated a divergent lineage from the closest neighbours in the genus Ruminococcus . The results of 16S rRNA sequence comparison, whole genome average nucleotide identity (ANI) and DNA G+C content data indicate that JE7A12 T represents a novel species which we propose the name Ruminococcus bovis with JE7A12 T as the type strain.